How the diversity of pastoralist livestock benefits rangelands - Tarawali, Shirley A. (International Livestock Research Institute, 2022)
Pastoralists have a symbiotic relationship with rangelands which creates opportunities for both productivity and environmental benefits. Shirley Tarawali, deputy director general of the International Livestock Research Institute (ILRI) and chair of the Global Agenda for Livestock (GASL), talks to us about the diversity of livestock with a focus on that pastoralist-rangelands relationship. ILRI and GASL are supporters of the resolution for the International Year of Rangelands and Pastoralists.